Cytosolic Glutamine Synthetase Isozymes Play Redundant Roles in Ammonium Assimilation Under Low-Ammonium Conditions in Roots of Arabidopsis thaliana. (24th January 2018) - Konishi, Noriyuki; Saito, Masahide; Imagawa, Fumi; Kanno, Keiich; Yamaya, Tomoyuki; Kojima, Soichi
Abstract: Ammonium is a major nitrogen source for plants; it is assimilated into glutamine via a reaction catalyzed by glutamine synthetase (GLN). Arabidopsis expresses four cytosolic GLN genes, GLN1; 1, GLN1; 2, GLN1; 3 and GLN1; 4, in roots. However, the function and organization of these GLN1 isozymes in ammonium assimilation in roots remain unclear. In this study, we aimed to characterize the four GLN1 isozymes. The levels of growth of the wild type and gln1 single and multiple knockout lines were compared in a hydroponic culture at ammonium concentrations of 0.1 and 3 mM. Under the low-ammonium concentration, in single mutants for each GLN1 gene, there was little effect on growth, whereas the triple mutant for GLN1; 1, GLN1; 2 and GLN1; 3 grew slowly and accumulated ammonium. Under the high-ammonium concentration, the single mutant for GLN1; 2 showed 50% decreases in fresh weight and glutamine, whereas the other gln1 single mutants did not show notable changes in the phenotype. The double mutant for GLN1; 1 and GLN1; 2 showed less growth and a lower glutamine concentration than the single mutant for GLN1; 2 . Promoter analysis indicated an overlapping expression of GLN1; 1 with GLN1; 2 in the surface layers of the roots. We thus concluded that: (i) at a low concentration, ammonium was assimilated by GLN1; 1, GLN1; 2 and GLN1; 3, and they were redundant; (ii) low-affinity GLN1; 2 could contribute to ammonium assimilation at concentrations ranging from 0.1 to 3 mM; and (iii) GLN1; 1 supported GLN1; 2 within the outer cell layers of the root.